The Business of Software: Owning and Using. - Armour, Phillip G. (Communications of the ACM, 2014)
The author conveys his thoughts about owning and using knowledge on vital and supporting systems. Topics discussed include software development as the driving force of the new economy, supporting knowledge and vital knowledge as the two kinds of operational capability that business enterprises need, and learning and creative activity as among the strongest motivators of software engineers if they have the opportunity to learn and develop something new.